Consequences of scarcity: the impact of perceived scarcity on executive functioning and its neural basis - Huang, Long; Li, Xiaojuan; Xu, Fuming; Li, Fuhong (Frontiers in Neuroscience, 2023)
Introduction Previous studies have found a causal relationship between scarcity and the adverse impact it has on executive functioning. However, few studies have directly examined perceived scarcity, and cognitive flexibility (the third component of executive functions) has rarely been included. Methods Using a 2 (group: scarcity group vs. control group) × 2 (trial type: repeat trial vs. switch trial) mixed design, this study directly explored perceived scarcity’s impact on cognitive flexibility and revealed its neural basis in the switching tasks. Seventy college students participated in this study through open recruitment in China. A priming task was used to induce perceived scarcity, thus exploring the impact of perceived scarcity on participants’ performance in switching tasks and enabling the analysis of the neural activity of the brain, combined with electroencephalograph (EEG) technology. Results In terms of behavioral outcomes, perceived scarcity led to poorer performance and a greater switching cost of reaction time in the switching tasks. Regarding neural activity, perceived scarcity led to an increase in the amplitude of P3 differential wave (repeat trials minus switch trials) in the parietal cortex during the target-locked epochs in the switching tasks. Discussion Perceived scarcity can lead to changes in the neural activity of the brain regions related to executive functioning, resulting in a temporary decrease in cognitive flexibility. It may lead to individuals unable to adapt well to the changing environment, unable to quickly devote themselves to new tasks, and reduce work and learning efficiency in daily life.